Influence of the Board of Commissioners, Board of Directors, Audit Committee, and Investment Opportunity Set on Financial Performance - Sri Maryati; Tiara Anggraini (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to empirically examine the effect of the board of commissioners, board of directors, audit committee, and investment opportunity set on financial performance. This study uses library and internet research methods, namely the financial reports of manufacturing companies listed on the IDX for 2019-2021. The data in this study were processed using SPSS 25. The results showed that the board of commissioners, board of directors, and audit committee had no effect on financial performance, but the investment opportunity set had a significant positive effect on financial performance.